(untitled) (Ibrahim Medical College Journal, 2009)
A retrospective study was done in the in-patient department of paediatrics, BIRDEM from January 2002 to November 2006 to determine the clinico-laboratory features, precipitating factors and outcome of diabetic ketoacidosis. Over the five year period, 344 diabetic patients were hospitalized. Among them, 54 (15.6%) had diabetic ketoacidosis (DKA). Among those, 50 were Type I, one was Fibrocalculous Pancreatic Diabetes (FCPD) and 3 were of other specific types. More than half (51.9%) of the patients were newly diagnosed. Amongst the precipitating factors, 28% had missed insulin and 48% had overt infection. Infections, particularly those of the respiratory tract, were the main precipitating cause for the DKA. There was h/o both infection and missed insulin injections in 11.5% patients. The mean age of patients with DKA was 11.2 ± 4.4 years. Those in the age range 10-14 yrs suffered most frequently (p<0.0001) from ketoacidosis (n= 38, 70.4%) compared with those aged 0-4 yrs (9%) and 5-9 yrs. (20%). There was a significant difference between those newly diagnosed (group I) and known diabetics (group II) (p<.029). The frequency of DKA was higher in girls than in boys (66.7% vs. 33.3%; p =.0001). The median duration of polyuria and/or polydipsia was variable between newly diagnosed and known diabetics (3.2 - 25d) (p<.001). All patients presented with altered levels of consciousness and 35 (67.3%) were unconscious of different grades. Mean random blood glucose (RBG) and HbA1c were 27.6mmol/L and 13.4%. Complications noted were acute renal failure (n=2, 3.7%) and cerebral edema (n = 4, 7.5%). The outcome of treatment in the whole group was good, 46 (86.7%) patients recovered without complications, but 7 (13.4%) patients died. Ibrahim Med. Coll. J. 2008; 2(1): 17-20 Key words: Ketosis, children, diabetes, BIRDEM doi: 10.3329/imcj.v2i1.2926